Molecular identity of the lateral lemniscus nuclei in the adult mouse brain - García-Guillén, Isabel M.; Aroca, Pilar; Marín, Faustino (Frontiers in Neuroanatomy, 2023)
The dorsal (DLL), intermediate (ILL), and ventral (VLL) lateral lemniscus nuclei are relay centers in the central auditory pathway of the brainstem, commonly referred to as the lateral lemniscus nuclei (LLN). The LLN are situated in the prepontine and pontine hindbrain, from rhombomeres 1 to 4, extending from the more rostral DLL to the caudal VLL, with the ILL lying in between. These nuclei can be distinguished morphologically and by topological and connectivity criteria, and here, we set out to further characterize the molecular nature of each LLN. We searched in situ hybridization studies in the Allen Mouse Brain Atlas for genes differentially expressed along the rostrocaudal axis of the brainstem, identifying 36 genes from diverse functional families expressed in the LLN. Available information in the databases indicated that 7 of these 36 genes are either associated with or potentially related to hearing disorders. In conclusion, the LLN are characterized by specific molecular profiles that reflect their rostrocaudal organization into the three constituent nuclei. This molecular regionalization may be involved in the etiology of some hearing disorders, in accordance with previous functional studies of these genes.